Disseminated rhino-orbital-cerebral mucormycosis in Philadelphia chromosome-positive mixed phenotype acute leukemia: a case report and literature review - Zhou, Yao; He, Meijuan; Zhang, Qiu; Yao, Jia; Wang, Zheng; Chen, Baoan; Guo, Jiamin; Gao, Fengming; Liu, Zefa (Frontiers in Medicine, 2025)
Rhino-orbital-cerebral mucormycosis (ROCM) is a rapidly progressing and life-threatening fungal infection caused by fungi in the order Mucorales. It predominantly affects immunocompromised individuals, such as those undergoing chemotherapy for hematological malignancies. Despite its high mortality rate, ROCM remains underrecognized, and its clinical features in patients with Philadelphia chromosome-positive (Ph+) mixed phenotype acute leukemia (MPAL) are rarely reported. This report describes a 48-year-old female who presented with a one-week history of fever without localized pain and was diagnosed with Ph+ MPAL by laboratory blood tests and comprehensive bone marrow examination. She was treated with imatinib and received acute lymphoblastic leukemia (ALL)-like chemotherapy, and used voriconazole to prevent fungal infections. On day 9 of admission, the patient developed fever and skin lesions on the right nasal area. The skin lesions spread rapidly, indicating a potentially aggressive infection. A pathological biopsy of the affected area confirmed the diagnosis of ROCM. We administered liposomal amphotericin B (L-AmB) in a timely manner and effectively controlled the infection. The most common fungal infections in Ph+ MPAL are Candida and Aspergillus. To the best of our knowledge, this is the first case of ROCM. Our case reports support the limitations of voriconazole in preventing Mucorales infections and emphasizes the importance of broad coverage in antifungal prevention strategies, early diagnosis, and timely treatment. In addition, we reviewed 27 other cases of rhinocerebral mucormycosis in patients with acute leukemia and provide an analysis of these cases.